Aunt Dimity and the widow's curse [large type] - Atherton, Nancy (Atherton, Nancy. Aunt Dimity series., 2017)
"Nancy Atherton's twenty-second cozy mystery in the beloved, nationally bestselling Aunt Dimity series. It's early April in the small English village of Finch. Lori Shepherd's husband and sons are spending Easter break camping, and Lori is perfectly happy to be left at home with Bess, spared a week of roughing it with a curious toddler. The two attend a village events committee meeting and Lori is astonished when the elderly, soft-spoken widow Mrs. Annabelle Craven stands to make an announcement: she's decided to hold a quilting bee in the old schoolhouse. At the quilting bee, Lori ends up seated beside Mrs. Craven, delighted at the opportunity to learn more about her neighbor's life in the village of Old Cowerton. But dear, sweet Mrs. Craven's stories reveal a startling secret about her first husband's death. With Aunt Dimity's advice, Lori sets out to learn the truth about what the residents of Old Cowerton refer to as the "widow's curse"--And the deeper she digs, the more horrifying the tale becomes, until she discovers the most astounding revelation of all"--